Pengaruh Ukuran Perusahaan Dan Pertumbuhan Penjualan Terhadap Financial Distress - Nasution, Ulfa Oktavani; Aprilia, Irdarena; Utami, Devina (Jurnal Ekonomi Manajemen Akuntansi Keuangan Bisnis Digital, 2024)
The research aims to test and analyze the influence of company size and sales growth on financial distress. Financial distress is a situation where a company can experience bankruptcy because it cannot fulfill its obligations and has small profits. Research population of banking sector entities for the 2019 – 2020 period listed on the Indonesian Stock Exchange. The non-probability sampling technique used a purposive sampling method with a total of 29 companies. The data analysis technique used is multiple regression analysis. The research results show that the sales growth variable has a significant effect on financial distress, meaning that management involvement and sales growth greatly influence financial distress. Company size has no effect on financial distress.